A low phase noise high power Er-fiber frequency comb synchronized to the hydrogen maser clock by harmonic phase locking - Li, Mingkun; Yang, Xiguang; Rao, Bingjie; Yan, Lulu; Chen, Xin; Yuan, Ru; Zhang, Pan; Zhang, Yanyan; Liu, Tao (Frontiers in Physics, 2023)
We demonstrate a low phase noise all polarization-maintaining (PM) Er-fiber optical frequency comb (OFC) with low phase noise, which is synchronized to the hydrogen maser clock (HMC) using the 18th harmonic of the repetition rate for tight phase locking. The instability of the locked carrier envelope offset frequency is 1.2410-18@1 s, the phase noise of the OFC is -96 dBc/Hz at 1Hz offset, and the corresponding RMS timing jitter of the repetition rate is 62 fs (1 Hz 1 MHz). The residual frequency instability of the repetition rate (200 MHz) is 1.4610-14@1s, and the residual phase noise of the OFC normalized to 10 MHz is -138 dBc/Hz at 1 Hz offset and declines to about -160 dBc/Hz at the far-end, much lower than that of the HMC (-122 dBc/Hz at 1 Hz and -156 dBc/Hz at the far-end).